2018
DOI: 10.1155/2018/7659243
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Glomerular and Tubular Damage in the Early Stage of Kidney Disease in Type 2 Diabetic Patients

Abstract: Diabetic kidney disease develops in half of genetically predisposed patients with type 2 diabetes (T2DM). Early diagnosis of kidney damage and nephroprotective treatment are the ways of preventing the disease progression. Our aim was to evaluate selected laboratory markers of glomerular and tubular damage in T2DM patients with early stages of chronic kidney disease (G1/G2, A1/A2) for their associations with A2 albuminuria and early decline in the estimated glomerular filtration rate (eGFR). Among 80 T2DM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 45 publications
4
51
1
7
Order By: Relevance
“…Although our diabetic subject had different average age, duration of disease, race and socioeconomic status, the result had high consistency with other studies and also demonstrated that NGAL and KIM-1 appeared earlier in nephropathy. 15,16,27,28,31,[35][36][37][38][39] Sensitivity and specificity of urine NGAL and KIM-1 in early diagnostic diabetic nephropathy of our study were similar to other researches. 39,40 Kapoula et al had showed the pooled sensitivity and specificity among the different settings analyzed ranged from 0.42 (95% CI, 0.22-0.66) to 1.00 (95% CI, 0.99-1.00) and 0.72 (95% CI, 0.62-0.80) to 0.98 (95% CI, 0.50-1.00) in T2DM patients, respectively.…”
Section: Dovepresssupporting
confidence: 90%
See 1 more Smart Citation
“…Although our diabetic subject had different average age, duration of disease, race and socioeconomic status, the result had high consistency with other studies and also demonstrated that NGAL and KIM-1 appeared earlier in nephropathy. 15,16,27,28,31,[35][36][37][38][39] Sensitivity and specificity of urine NGAL and KIM-1 in early diagnostic diabetic nephropathy of our study were similar to other researches. 39,40 Kapoula et al had showed the pooled sensitivity and specificity among the different settings analyzed ranged from 0.42 (95% CI, 0.22-0.66) to 1.00 (95% CI, 0.99-1.00) and 0.72 (95% CI, 0.62-0.80) to 0.98 (95% CI, 0.50-1.00) in T2DM patients, respectively.…”
Section: Dovepresssupporting
confidence: 90%
“…40 Zylka et al had found sensitivity of NGAL and KIM-1 were 80%, 79%, respectively, and specificity of NGAL, KIM −1 was 61%, 51%, respectively. 39 Based on these values, urinary NGAL and KIM-1 could be used as independent markers for diagnostic and prediction for diabetic nephropathy.…”
Section: Dovepressmentioning
confidence: 99%
“…In addition, it is a sensitive and early indicator of pathological changes in the kidneys exposed to nephrotoxic xenobiotics. 23 The increased release of lysosomal enzymes from renal tubular epithelial cells that we observed in our study may indicate an ongoing inflammatory process in the kidneys, as the rising number of lysosomes in tubular cells reflects defense mechanisms of kidney cells.…”
Section: Methodsmentioning
confidence: 57%
“…Proteinuria and albuminuria induce proximal tubular injury, leading to interstitial fibrosis, and are seen as independent risk factors for reducing renal function. The other markers that indicate the early progression of kidney diseases are neutrophil gelatinase associated lipocalin and angiopoietin-2 [25][26][27]. Although we could not measure urinary albumin levels and these early indicators, both groups showed overt proteinuria suggesting kidney injury in our model had already progressed to some degree.…”
Section: Discussionmentioning
confidence: 79%